Presence of blaCTXM-1, blaCTXM-9, and blaTEM-1 Genes in Extended-spectrum β-lactamase-producing Escherichia coli Isolates from Hospital Wastewater - Charlene Princess Salvador Tolenada; Geraldine Budomo Dayrit (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC) are selectively proliferated in the human gut, excreted through feces, and deposited through wastewater lines, with hospital wastewater acting as a major reservoir of antibiotic resistance genes and resistant bacteria, thus pose adverse effects to human health. This study aimed to determine the presence of blaCTXM-1, blaCTXM-9, blaTEM-1, and blaSHV-1 genes in ESBL-EC in wastewater from selected hospitals in Manila and Quezon City, the Philippines.METHODS: Influent and effluent in twelve hospital wastewater treatment plants were collected, screened for cefotaxime-resistant E. coli, and examined for the ESBL production through phenotypic characterization using conventional bacterial identification, disk diffusion method, and VITEK® 2 Compact system and genotypic identification of ESBL-EC blaCTXM-1, blaCTXM-9, blaTEM-1, blaSHV-1 genes using multiplex polymerase chain reaction (PCR).RESULTS: Conventional bacterial identification methods and the VITEK® 2 Compact system results showed that both influent and effluent samples were positive for ESBL-EC at 33.3% and 16.7%, respectively. Multiplex PCR results revealed that various E. coli isolates were of ESBL-EC blaCTXM-1, blaCTXM-9, and blaTEM-1 genes. Multi-drug resistance was observed among all ESBL-EC isolates with resistance being highest against ampicillin, cefuroxime, ceftazidime, ceftriaxone, cefepime, piperacillin, and aztreonam.CONCLUSION: As the study revealed the presence of ESBL-producing bacteria, efforts must be made to ensure the prudent antimicrobial use with possible emphasis on antibiotic rotation accompanied by intensified infection prevention and control in hospital settings.KEYWORDS: antimicrobial resistance, beta-lactams, blaCTXM, blaTEM, extended-spectrum beta-lactamase, E. coli, hospital wastewater